Building Moral Awareness through Civic Education: An Analysis of Social-Emotional Characters in the Digital Age - Pandikar; Elih Sujana; Ridwan Hadi (Gema Cendekia Institute, 2025)
The rapid development of digital technology has reshaped the moral landscape of young citizens, challenging traditional approaches to civic and moral education. This study explores how Civic Education (Pendidikan Kewarganegaraan) can cultivate moral awareness through the integration of social-emotional character development in the digital era. Using a qualitative descriptive approach and literature-based analysis, the research synthesizes theoretical perspectives from moral philosophy, social-emotional learning (SEL), and digital citizenship frameworks. The findings reveal that moral awareness is not merely a cognitive competence but a multidimensional construct involving empathy, digital responsibility, and ethical reflection. Civic Education serves as a strategic platform for nurturing these dimensions by embedding digital ethics, emotional literacy, and community-based learning in classroom practices. The study also emphasizes the importance of character-based digital literacy to counter online disinformation, cyberbullying, and moral disengagement. In conclusion, the article proposes a transformative model of Civic Education that integrates moral awareness with socio-emotional intelligence, enabling learners to act responsibly and compassionately in digital society. This model contributes to the broader discourse on education for sustainable moral development and supports the realization of SDG 4.7 concerning global citizenship and sustainable values.